Hypophosphatemia after Right Hepatectomy for Living Donor Liver Transplantation - Kelly W Burak; Charles B Rosen; Jeff L Fidler; Gina K Hesley; David Nagorney; Michael R Charlton; David J Brandhagen (Canadian Journal of Gastroenterology)
Hypophosphatemia has been described in patients undergoing right hepatectomy for liver cancer and in living donors for liver transplantation who also received total parenteral nutrition. At the study centre, significant hypophosphatemia (0.36 mmol/L or less) requiring intravenous replacement was seen in two of the first nine living donors for adult-to-adult liver transplantation. To determine the frequency of hypophosphatemia in living donors, the authors obtained phosphate levels on stored serum samples from postoperative days 0, 1, 3 and 7 in all nine patients, none of whom were on total parenteral nutrition. Within the first week, hypophosphatemia developed in 55.6% of patients and phosphate levels returned to normal by day 7 in all nine patients. One patient had normal phosphate levels during the first week, but had profound hypophosphatemia (0.32 mmol/L) on day 14 when he presented with a Staphylococcus aureus infection of a bile collection and significant hypoxemia. The extent of hepatectomy and the rate of liver regeneration, estimated by baseline and postoperative day 7 volumetric computed tomography scans, did not correlate with the development of hypophosphatemia. In conclusion, hypophosphatemia is common in living donors undergoing right hepatectomy and may be associated with complications. All living donors should be monitored for the development of hypophosphatemia during the first two postoperative weeks.